Implementation method for improving high-temperature chemical stability and mechanical compatibility of transition metal silicon boride coating

By using two-step chemical vapor deposition technology to form a boron-doped multilayer structure on the surface of the transition metal, the problem of insufficient oxidation resistance and mechanical compatibility of the multi-layer boroside coating at high temperatures is solved, and the high-temperature chemical stability and mechanical compatibility of the coating are improved.

CN120505588AActive Publication Date: 2025-08-19SHANGHAI JIAOTONG UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511006089.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-22
Publication Date
2025-08-19
Estimated Expiration
2045-07-22

AI Technical Summary

Technical Problem

The existing multi-layer borosilicate coatings cannot have both oxidation resistance and diffusion resistance at high temperatures, and the coating is prone to cracks or fall off due to differences in thermal expansion coefficient and Young's modulus from the matrix.

Method used

Using a two-step chemical vapor deposition technology, a dense continuous boride layer is first introduced on the surface of the transition metal, and then an ordered multi-layer structure is formed through silicon-boron co-deposition and preoxidation treatment, including a boron-doped silicon dioxide layer, a silicide layer and a boride layer, forming a good performance matching to improve mechanical compatibility and chemical stability.

Benefits of technology

It improves the high-temperature chemical stability and mechanical compatibility of the coating, prevents antioxidant elements from entering the matrix, enhances the self-healing and oxidation resistance of the coating, reduces the layering driving force between the coating and the matrix, and improves the overall performance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120505588A_ABST
    Figure CN120505588A_ABST
Patent Text Reader

Abstract

The invention relates to an implementation method for improving high-temperature chemical stability and mechanical compatibility of a transition metal silicon boride coating. The method comprises the following steps: carrying out chemical vapor deposition on the surface of transition metal to obtain a boride layer; a boron-doped transition metal silicide layer is obtained through chemical vapor deposition; and finally, carrying out pre-oxidation treatment to obtain a composite structure of a boron-doped silicon dioxide layer, three boron-doped transition metal silicide layers, two transition metal boride layers and a molybdenum matrix. Through a two-step chemical vapor deposition technology, compact and continuous boride layers are introduced in sequence, and good performance matching is formed between the compact and continuous boride layers and an ordered multi-layer structure obtained through subsequent silicon-boron co-deposition and pre-oxidation so as to improve mechanical compatibility; and a rich boron source and the silicide layer are provided to form a transition metal silicon boride layer with good element diffusion resistance so as to improve the chemical stability of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a technology in the field of new material coatings, specifically a method for improving the high-temperature chemical stability and mechanical compatibility of transition metal silicon boride coatings. Background Art

[0002] Existing technologies generally use multilayer borosilicate coatings to protect refractory metals, refractory high-entropy alloys (RHEAs), or refractory multi-principal element alloys (RMPEAs) at high temperatures (1600°C). However, multilayer borosilicate coatings fail to simultaneously enhance the oxidation resistance and diffusion resistance of the silicide layer, and fail to consider the high-temperature mechanical compatibility of the multilayer structure. Silicide coatings that are not doped with boron do not provide protection over a wide temperature range, and the multilayer silicide layers formed after oxidation also lack good oxidation resistance at high temperatures. Summary of the Invention

[0003] The present invention addresses the shortcomings of existing borosilicate coatings, such as the inability of existing borosilicate coatings to combine antioxidant properties and diffusion resistance, and the fact that differences in thermal expansion coefficient and Young's modulus with the substrate may lead to cracks or even peeling of the coating. A method for improving the high-temperature chemical stability and mechanical compatibility of transition metal borosilicate coatings is proposed. A two-step chemical vapor deposition technique is used, in which a dense and continuous boride layer is introduced through the first step of boron deposition, forming a good performance match with the ordered multilayer structure obtained by subsequent silicon-boron co-deposition and pre-oxidation to improve mechanical compatibility. A rich boron source is also provided to form a transition metal borosilicate layer with a silicide layer having good elemental diffusion resistance to improve the chemical stability of the coating.

[0004] The present invention is achieved through the following technical solutions:

[0005] The present invention relates to a method for improving the high-temperature chemical stability and mechanical compatibility of a transition metal silicon boride coating. The method comprises the following steps: obtaining a boride layer on a transition metal surface by chemical vapor deposition; then obtaining a boron-doped transition metal silicide layer by chemical vapor deposition; and finally obtaining a composite structure of a boron-doped silicon dioxide layer, three boron-doped transition metal silicide layers, two transition metal boride layers, and a molybdenum substrate by pre-oxidation treatment.

[0006] The transition metals are molybdenum metal, niobium metal, tantalum metal and tungsten metal.

[0007] The boride layer is obtained by chemical vapor deposition, which means that boron deposition diffusion source powder is filled around the transition metal and then heated and kept warm in an inert gas atmosphere.

[0008] The boron-doped transition metal silicide layer obtained by chemical vapor deposition is obtained by filling silicon-boron co-deposited diffusion source powder around the transition metal containing the boride layer and then heating and keeping the mixture warm in an inert gas atmosphere.

[0009] The silicon-boron co-deposition diffusion source powder preferably has a silicon / boron mass fraction ratio of 45:1-2.5:1, preferably 34:1.

[0010] The pre-oxidation treatment is to heat the transition metal containing the boron-doped transition metal silicide layer to a pre-oxidation temperature below the service temperature in an air atmosphere and keep the temperature.

[0011] The present invention relates to a transition metal borosilicate coating prepared by the above method, comprising: a boron-doped silicon dioxide layer, a boron-doped transition metal silicide anti-oxidation layer, a transition metal borosilicate first diffusion barrier layer and a transition metal boride second diffusion barrier layer.

[0012] The present invention relates to the application of the transition metal borosilicate coating, which is used for protecting new high-temperature structural materials in high-temperature oxygen-containing environments.

[0013] Technical Effects

[0014] The present invention performs a one-step boronizing and then silicon-boron co-diffusion on the surface of a refractory transition metal alloy, and undergoes a pre-oxidation treatment to obtain a thick and dense boride layer, which acts as an initial element diffusion barrier before the diffusion barrier layer (silicon boride layer) is formed to prevent the antioxidant element silicon from entering the substrate, and increases the thickness and density of the diffusion barrier layer (silicon boride layer), thereby improving the full-cycle thermochemical stability of the coating; the second step of silicon-boron co-diffusion obtains a boron-doped silicide layer, thereby improving its self-healing and oxidation resistance; the pre-oxidation obtains a boron-doped silicon dioxide layer, a layered boron-doped silicide layer, a silicon boride diffusion barrier layer, and a layered boride layer to form a gradient coating, thereby improving the mechanical compatibility of the overall coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Schematic diagram of the coating structure of the present invention;

[0016] Figure 2 (a) is the X-ray diffraction pattern of the sample surface after boron deposition in the embodiment; (b) is the backscattered electron image of the cross section of the sample after boron deposition;

[0017] Figure 3 (a) is a backscattered electron image of a cross section of a sample after silicon-boron co-deposition in the embodiment; (b) is a backscattered electron image of a cross section of a sample after pre-oxidation; the inset is a partially enlarged backscattered electron image of the cross section;

[0018] Figure 4The mass change curve of the sample in the embodiment during the isothermal oxidation test at 1500°C;

[0019] Figure 5 This is a phase distribution image of the cross section of the sample in the embodiment after isothermal oxidation at 1500°C for 100 hours;

[0020] Figure 6 (a) shows the mass change of the sample in the embodiment after isothermal oxidation at 1600°C for 20 h; (b) shows the corresponding phase distribution image of the sample cross section;

[0021] Figure 7 This is a cross-sectional phase distribution image of a sample without boron deposition in the embodiment after isothermal oxidation at 1600°C for 20 hours;

[0022] Figure 8 is the delamination driving force curve of the multilayer coating in the early stage of oxidation;

[0023] Figure 9 is the delamination driving force curve of the multilayer coating in the late oxidation stage;

[0024] Figure 10 Schematic diagram of the effects of different proportions of silicon-boron co-deposition diffusion source powder. DETAILED DESCRIPTION

[0025] like Figure 1 As shown, this embodiment relates to a method for improving the high-temperature chemical stability and mechanical compatibility of a transition metal borosilicate coating, comprising:

[0026] Step 1: Prepare boron deposition diffusion source powder: grind 5wt.% boron powder, 2.5wt.% sodium fluoride powder as an activator, and 92.5wt.% alumina powder for 20 minutes and mix well;

[0027] Step 2, chemical vapor deposition (boron deposition), specifically includes:

[0028] 2.1 The pure molybdenum sample was polished step by step with 400#, 800#, 1500#, 2000#, 3000#, 5000#, and 7000# sandpaper, ultrasonically cleaned in anhydrous ethanol for 10 minutes, dried with cold air, and placed in the middle of a corundum crucible. The crucible was filled with the powder prepared in step 1 and compacted, and placed in a tube furnace;

[0029] 2.2 Under argon environment, set the heating rate to 10℃ / min. When the temperature rises to 1000℃, keep it warm for 3h. Then cool it with the furnace. After the temperature drops to room temperature, take it out and ultrasonically clean it in alcohol for 30min. After drying with cold air, the following is prepared: Figure 2 (a) and (b) show a molybdenum boride (MoB) layer with a thickness of approximately 19 μm;

[0030] Step 3: Prepare silicon-boron co-deposition diffusion source powder: grind 34 wt.% silicon powder, 1 wt.% boron powder, 2.5 wt.% sodium fluoride powder as an activator, and 62.5 wt.% aluminum oxide powder for 20 minutes and mix well;

[0031] Step 4, chemical vapor deposition (silicon-boron co-deposition), specifically includes:

[0032] 4.1 Place the sample processed in step 2 in the middle of a corundum crucible, fill and compact the surrounding area with the powder prepared in step 3, and place it in a tube furnace;

[0033] 4.2 Under argon atmosphere, set the heating rate to 10℃ / min. When the temperature reaches 1000℃, keep it warm for 50h. Then cool it down with the furnace. After the temperature drops to room temperature, take it out and ultrasonically clean it in alcohol for 30min. After drying with cold air, the following is prepared: Figure 3 (a) shows a molybdenum disilicide (MoSi2) layer with a thickness of about 64 μm and a MoB layer of about 23 μm between the MoSi2 layer and the molybdenum substrate;

[0034] Step 5, pre-oxidation treatment: Place the sample treated in step 4 in a corundum crucible and place it in a tube furnace; in an air atmosphere, set the heating rate to 10℃ / min, and when the temperature rises to 1500℃, keep it warm for 10h; then cool it with the furnace, and after the temperature drops to room temperature, prepare the following Figure 3 (b) and Figure 1 The structure shown is a composite structure of a boron-doped silicon dioxide layer, a boron-doped MoSi2 layer, a boron-doped Mo5Si3 anti-oxidation layer T1, a Mo5SiB2 diffusion barrier layer T2, a MoB layer, a Mo2B layer and a molybdenum substrate from the outside to the inside.

[0035] Performance testing:

[0036] A) The composite structures obtained from steps 1 to 5 are subjected to isothermal oxidation at 1500°C. The obtained oxidation mass change curve is as follows: Figure 4 As shown in Figure 2, the average unit surface area mass gain after oxidation at 1500 °C for 100 h is 2.23 mg / cm 2 ;

[0037] like Figure 5 As shown in the figure, the phase analysis results show that the diffusion barrier layer T2 is dense and continuous, and there is a dense and continuous Mo2B layer between it and the substrate. There is no phenomenon of the antioxidant element Si entering the substrate, indicating that the coating has good chemical stability.

[0038] B) The two composite structures obtained from steps 1 to 5 were isothermally oxidized at 1600°C for 20 hours, and the oxidation mass changes were as follows: Figure 6As shown in (a), the unit surface area mass increase after oxidation is 1.47 mg / cm 2 and 1.96 mg / cm 2 ;

[0039] like Figure 6 (b) shows the phase composition of the coating cross section after isothermal oxidation at 1600℃ for 20h. Figure 5 Similarly, no Si element diffusion into the substrate was observed, which further indicates that the coating has excellent high-temperature chemical stability;

[0040] C) The sample without boron deposition but only silicon-boron deposition (one-step sample) was isothermally oxidized at 1600℃ for 20h. The cross-sectional phase distribution image of the sample is shown as follows: Figure 7 As shown, compared with Figure 6 (b) The two-step sample represented by the diffusion barrier layer T2 is obviously thinner and discontinuous; there are obvious anti-oxidation layers T1 and Mo3Si layers between the diffusion barrier layer T2 and the substrate, which means that Si diffuses into the molybdenum substrate, indicating that this coating does not have good chemical stability at high temperatures.

[0041] like Figure 8 As shown in Figure 2, the maximum delamination driving force of the two samples in the initial oxidation stage (with the presence of MoSi2 layer) is 267 J / m 2 However, the maximum value of the one-step sample appears at the coating / substrate interface, while that of the two-step sample appears at the Mo2B layer / diffusion barrier layer T2 interface; the delamination driving force of the coating / substrate interface of the two-step sample is only 237 J / m 2 , which was reduced by 11.2% compared with the one-step sample, indicating that the coating prepared by the two-step method has better mechanical compatibility and lower delamination tendency;

[0042] like Figure 9 As shown in Figure 2, the maximum delamination driving force of the one-step sample in the late oxidation stage (MoSi2 is completely converted to T1) is 224 J / m 2 , while the maximum delamination driving force of the two-step sample is only 206 J / m 2 , which is reduced by 8.0%, and the position is also located at the interface of Mo2B layer / diffusion barrier layer T2; the delamination driving force of the coating / substrate interface of the two-step sample is only 172J / m 2 , which is reduced by 23.2% compared with the one-step sample, which further shows that the coating prepared by the two-step method has stronger mechanical compatibility.

[0043] like Figure 10The figure shows the effect of different ratios of silicon-boron co-deposition diffusion source powder on the performance of the final MoB product. Among them, 30 / 5 and 25 / 10 cannot significantly improve the thickness and density of the MoB layer between the substrate and MoSi2, and will significantly increase the number of MoB particles in the MoSi2 layer, resulting in a decrease in coating viscosity and poor stability.

[0044] In summary, the present invention utilizes a two-step chemical vapor deposition technique to introduce a continuous and dense transition metal boride layer between the transition metal-silicon-boron coating and the substrate, which can act as an anti-diffusion layer before the transition metal silicon boride anti-diffusion layer is formed, and provide a rich boron source during long-term service, thereby improving the thickness and density of the transition metal silicon boride anti-diffusion layer, thereby improving the high-temperature chemical stability of the coating; the difference in thermal expansion coefficient between the transition metal boride layer and the substrate is small, thereby improving the high-temperature mechanical compatibility of the coating.

[0045] The above-mentioned specific implementation can be partially adjusted in different ways by those skilled in the art without departing from the principles and purpose of the present invention. The scope of protection of the present invention shall be based on the claims and shall not be limited by the above-mentioned specific implementation. All implementation schemes within its scope shall be subject to the constraints of the present invention.

Claims

1. A method for improving the high-temperature chemical stability and mechanical compatibility of a transition metal borosilicate coating, characterized in that: A boride layer is obtained by chemical vapor deposition on the surface of a transition metal; a boron-doped transition metal silicide layer is then obtained by chemical vapor deposition; and finally, a composite structure of a boron-doped silicon dioxide layer, three boron-doped transition metal silicide layers, two transition metal boride layers and a molybdenum substrate is obtained by pre-oxidation treatment.

2. The method for improving the high-temperature chemical stability and mechanical compatibility of a transition metal borosilicate coating according to claim 1, wherein: The boride layer is obtained by chemical vapor deposition, which means that boron deposition diffusion source powder is filled around the transition metal and then heated and kept warm in an inert gas atmosphere.

3. The method for improving the high-temperature chemical stability and mechanical compatibility of a transition metal borosilicate coating according to claim 2, wherein: The boron deposition diffusion source powder comprises boron powder, sodium fluoride activator powder and aluminum oxide powder.

4. The method for improving the high-temperature chemical stability and mechanical compatibility of a transition metal borosilicate coating according to claim 1, wherein: The boron-doped transition metal silicide layer obtained by chemical vapor deposition is obtained by filling silicon-boron co-deposited diffusion source powder around the transition metal containing the boride layer and then heating and keeping the mixture warm in an inert gas atmosphere.

5. The method for improving the high-temperature chemical stability and mechanical compatibility of a transition metal borosilicate coating according to claim 4, wherein: The silicon-boron co-deposition diffusion source powder comprises silicon powder, boron powder, sodium fluoride activator powder and aluminum oxide powder.

6. The method for improving the high-temperature chemical stability and mechanical compatibility of a transition metal borosilicate coating according to claim 4 or 5, characterized in that: The silicon-boron co-deposition diffusion source powder has a silicon / boron mass fraction ratio of 45:1 to 2.5:

1.

7. The method for improving the high-temperature chemical stability and mechanical compatibility of a transition metal borosilicate coating according to claim 1, wherein: The pre-oxidation treatment is to heat the transition metal containing the boron-doped transition metal silicide layer to a pre-oxidation temperature below the service temperature in an air atmosphere and keep the temperature.

8. The method for improving the high-temperature chemical stability and mechanical compatibility of a transition metal borosilicate coating according to claim 2 or 3, characterized in that: The heating and heat preservation under an inert gas atmosphere refers to: in an argon environment, setting the heating rate to 10°C / min, when the temperature is raised to 1000°C, keeping the temperature for 50 hours and then cooling with the furnace.

9. The method for improving the high-temperature chemical stability and mechanical compatibility of a transition metal borosilicate coating according to claim 7, wherein: The heating in air atmosphere means that in air atmosphere, the heating rate is set to 10°C / min, and when the temperature is raised to 1500°C, it is kept at this temperature for 10 hours and then cooled with the furnace.

10. A composite structure prepared according to the method according to any one of claims 1 to 9, characterized in that: include: From outside to inside, the boron-doped silicon dioxide layer, the boron-doped transition metal silicide anti-oxidation layer, the transition metal silicon boride first diffusion barrier layer and the transition metal boride second diffusion barrier layer.

Citation Information

Patent Citations

  • Penetrating agent of B-modified MoSi2 coating on surface of refractory metal and preparation method of coating

    CN108034922A

  • Implementation method of integrated ultrahigh-temperature environmental barrier composite coating

    CN119352016A

  • Protective coating on refractory metals

    GB934542A

  • Mo-Si-B-BASED COATINGS FOR CERAMIC BASE SUBSTRATES

    US20130157064A1